Implementation of effective alcohol control strategies is needed at large sports and entertainment events - Mark Lyne; Andrew Galloway (Elsevier, 2012)
Abstract Objective: To assess the implementation and effectiveness of strategies and actions to eliminate and/or reduce alcohol‐related problems at large sports and entertainment events in New Zealand. Methods: We conducted site visits and monitoring observations at venues before, during and after a variety of large events between March 2009 and November 2010. Thirteen events were attended at nine different venues. Events included rugby, rugby league and cricket matches, motor racing, rowing, horse racing, an outdoor music festival, and food and wine festivals. Results: Most large events appeared to pass with few or no alcohol‐related problems. The exceptions were one of the horse‐race meetings, a rugby league match and one food and wine festival. Common contexts at events where alcohol‐related problems were seen included: inadequate alcohol control and management by security staff; the ability to purchase four alcoholic drinks (rather than two) at a time; inexperienced bar staff untrained in responsible alcohol service; no or little promotion of low and non‐alcoholic drinks; and a lack of monitoring and enforcement of the law on intoxication. Conclusions: An important approach to prevent and reduce alcohol‐related problems at large spots and entertainment events is the use of specific alcohol‐control strategies. The management of alcohol consumption is a major part of event management that must be planned with harm‐minimisation strategies well in advance of the event itself. Implications: If strategies and actions are not properly implemented to manage the sale and supply of alcohol at large events, there is significant risk of alcohol‐related problems and harm resulting from them.